139k views
2 votes
Divide x^4 + 2x^2 + 1 by x+1 .​

1 Answer

4 votes

Answer:


=x^3-x^2+3x-3+(4)/(x+1)

Explanation:


(x^4+2x^2+1)/(x+1)\\\mathrm{Divide}\:(x^4+2x^2+1)/(x+1):\quad (x^4+2x^2+1)/(x+1)=x^3+(-x^3+2x^2+1)/(x+1)\\=x^3+(-x^3+2x^2+1)/(x+1)\\\mathrm{Divide}\:(-x^3+2x^2+1)/(x+1):\quad (-x^3+2x^2+1)/(x+1)=-x^2+(3x^2+1)/(x+1)\\=x^3-x^2+(3x^2+1)/(x+1)\\\mathrm{Divide}\:(3x^2+1)/(x+1):\quad (3x^2+1)/(x+1)=3x+(-3x+1)/(x+1)\\=x^3-x^2+3x+(-3x+1)/(x+1)\\\mathrm{Divide}\:(-3x+1)/(x+1):\quad (-3x+1)/(x+1)=-3+(4)/(x+1)\\=x^3-x^2+3x-3+(4)/(x+1)

User Abderrahmane
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.